Pirandello in context - Gaborik, Patricia (Cambridge University Press, 2024)
For students of Luigi Pirandello's life and works, this volume provides a multi-faceted view spanning the many genres in which he wrote, from poetry and essays to fiction and drama. It gives a true sense of Pirandello's remarkable sensitivity to place - from his native Sicily to Germany and Latin America - and of how his perspective was shaped by a wide range of interlocutors with varying professional backgrounds, from contemporary philosophers to fellow playwrights like Bernard Shaw, directors like Max Reinhardt and the actress Marta Abba. Diverse contributors explore the sheer genre-bending originality of Pirandello's humor, metatheatre, and fantastic tales, and reveal how profound shifts in society, culture, and politics in his time - Freud, Futurism, Fascism - conditioned not just his thought but also his meteoric rise to fame. A final section is dedicated to Pirandello's legacy in literature and drama throughout the twentieth century and into the twenty-first
Title from publisher's bibliographic system (viewed on 14 Mar 2024)
Sicily / Beatrice Alfonzetti -- Rome / Simona Costa -- Germany / Michael Subialka -- France / Anna Frabetti -- The United States / Marella Feltrin- Marella Feltrin-Morris -- Latin America / Stefano Boselli -- Publishing / Francesca Billiani -- Little theatres / Mirella Schino -- National theatres / S.E. Wilmer -- The Royal Italian Academy / Guido Bonsaver -- Marta Abba / Pietro Frassica -- Massimo Bontempelli / Patricia Gaborik -- Gian Francesco Malipiero / Anna Harwell Celenza -- Georges Pitoëff / Anna Frabetti -- Max Reinhardt / Michael Rössner -- George Bernard Shaw / John A. Bertolini -- Benedetto Croce / Pierpaolo Antonello -- Humor / Walter Pedullà -- Dialect theatre / Antonella Ottai -- Metatheatre / Mary Ann Frese Witt -- The fourth wall / W. B. Worthen -- The anti-character / Stefano Jossa -- Myth / Michael Bell -- The fantastic / Gabriele Pedullà -- History / Daniela Bini -- Celebrity / Lisa Sarti -- Cinema / Michael Syrimis -- Modernity / Michael Subialka -- Fascism / Patricia Gaborik -- Women / Daniela Bini -- Religion / Robert Pogue Harrison and Laura Wittman -- Madness / Valeria Paola Babini -- Suicide / Thomas Harrison -- Critical foundations / Giulio Ferroni -- Avant-garde theatre after Pirandello / Cindy Rosenthal -- Cinema after Pirandello / Robert S.C. Gordon
Keywords: Pirandello, Luigi -- 1867-1936 -- Criticism and interpretation; Pirandello, Luigi -- 1867-1936 -- Influence